Modeling, analysis and optimization of the rear axle of cereal combine harvester under real loads using finite elements method - Rezaei, Azam; Masoudi, Hassan; Zaki Dizaji, Hassan; Khorasani Ferdavani, Mohamad Esmail (Journal of agricultural engineering (Pisa, Italy), 2023)
Cereals combine harvester is one of the agricultural machines that works in difficult conditions and different forces are applied to its parts. The purpose of this study was to analyze static and dynamic loads on the rear axle of JD955 combine harvester to optimize it. First, real loads on the axle were measured by a special electronic system in stationary and moving modes in roads and farm with various forward speeds. Then, geometric model of the axle was designed in the CATIA software. Finally static, harmonic, transient and dynamic analysis were performed using finite element method in the ANSYS Workbench software. Mean of maximum loads on the axle in stopped mode, asphalt road, dirt road and inside the farm (while moving parallel and perpendicular to the farrows and turning in farm end) were equal to 15.067, 18.830, 49.167, 21.428, 27.07 and 27.857 KN, respectively. There was relatively linear relationship between the axle load and deformation. At the maximum load of 49.167 KN, the maximum von Mises stresses of 1200, 85.848, 21.392 and 1.754e-14 MPa were obtained in static, transient, dynamic and harmonic analyzes, respectively. Since structural errors in the axle were numerically close to zero, so the calculated stress values had good accuracy. The axle fatigue life for most of the loads was equal to the ideal value of 106 cycles. The least fatigue safety factor were obtained from 0.072 to 0.745 in static analysis and from 0.174 to 1.029 in linear transient analysis. According to the results of the analysis, it was necessary to optimize the existing design of axle. So, a rectangular piece was suggested as the suitable design for the JD955 rear axle middle section.